1997
DOI: 10.1093/humrep/12.7.1434
|View full text |Cite
|
Sign up to set email alerts
|

Two successful pregnancies in a 46,XY patient

Abstract: Two successful pregnancies (singleton followed by twins) following ovum donation/in-vitro fertilization in a 46,XY woman have been studied. Although similar cases have previously been presented: in a pure XY patient and in a 45,X/46,XY patient, this case is one in which a subsequent successful pregnancy has resulted. In such patients, the rate of Caesarean section appears to be increased, and we postulate that the hypoplastic nature of the uterus, although able to respond quite well to both exogenous and endog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 1 publication
1
20
0
Order By: Relevance
“…The presence of the XY genotype and H-Y antigen does not affect normal uterine and endometrial response, and the possibility of maintaining a normal pregnancy and delivery confirms the physiological ability of the uterus to accommodate and maintain a successful pregnancy in patients with XY dysgenesis (6). However, the literature reports fewer than 12 full-term pregnancies in patients with Swyer syndrome (7)(8)(9)(10)(11)(12)(13)(14). It is quite clear that we need reports on pregnancy outcomes in patients with Swyer syndrome to expand our knowledge and define better any specific risks in this unique patient population.…”
Section: Discussionmentioning
confidence: 82%
“…The presence of the XY genotype and H-Y antigen does not affect normal uterine and endometrial response, and the possibility of maintaining a normal pregnancy and delivery confirms the physiological ability of the uterus to accommodate and maintain a successful pregnancy in patients with XY dysgenesis (6). However, the literature reports fewer than 12 full-term pregnancies in patients with Swyer syndrome (7)(8)(9)(10)(11)(12)(13)(14). It is quite clear that we need reports on pregnancy outcomes in patients with Swyer syndrome to expand our knowledge and define better any specific risks in this unique patient population.…”
Section: Discussionmentioning
confidence: 82%
“…6 Only Kan et al and Selvaraj et al reported failed induction while Siddique et al and Michala et al reported successful vaginal delivery in three cases. 4,9,11,15 The hypoplastic uterus responds well to hormonal therapy and it may have anatomical ability to permit normal dilatation and labor however more reports with vaginal delivery would be required to support that.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas patients with a 45,X cell line are at risk for aortic dissection and rupture during pregnancy, even in the absence of demonstrable cardiovascular anomalies (e.g., aortic dilation, coarctation, or bicuspid aortic valve) (13), those with non-mosaic pure 46,XY gonadal dysgenesis do not appear to be at increased risk for adverse pregnancy outcomes other than cesarean delivery. However, fewer than 12 successful pregnancies in patients with Swyer syndrome have been described in the literature (3)(4)(5)(6)(7)(8)(9)(10)(11). Consequently, reports of pregnancy outcomes in patients with Swyer syndrome clearly are needed to expand our knowledge and better define any specific risks in this unique patient population.…”
Section: Discussionmentioning
confidence: 99%
“…Gonadectomy is recommended at time of diagnosis due to the risk for malignant transformation in the gonadal streaks (1,2). A small number of successful pregnancies achieved with oocyte donation have been reported in patients with 46,XY gonadal dysgenesis (3)(4)(5)(6)(7)(8)(9)(10)(11). We add to that record here by reporting a successful pregnancy in a patient with Swyer syndrome after transfer of frozen-thawed embryos derived from donor oocytes.…”
mentioning
confidence: 90%